Cold-spray bonding mechanisms and deposition efficiency prediction for particle/substrate with distinct deformability. (5th November 2016) - Meng, Fanchao; Hu, Dianyin; Gao, Ye; Yue, Stephen; Song, Jun
Abstract: Cold-spray involving particle and substrate that are of distinct deformability, i.e., soft (particle)/ hard (substrate) and hard (particle)/ soft (substrate) systems, has been investigated using systematic numerical simulations. For the soft/hard system, the bonding and deposition is dominantly controlled by particle plasticity. In contrast, physical trapping and mechanical interlocking play an important role for the hard/soft system. Employing a layered-particle/substrate model and a crater-particles model, we demonstrated the operation and playoff of different bonding mechanisms, and provided predictive assessments of the deposition efficiency that correspond well to experimental measurements. The present study offers key mechanistic insights towards rational process design of cold-spray. Graphical abstract: Highlights: Cold-spray of particle/substrate with distinct deformability has been investigated. Deposition is controlled by particle plasticity for soft particle/hard substrate. Trapping and interlocking in hard particles/soft substrate is elucidated via numerical simulations. The operation and playoff of different bonding mechanisms is demonstrated. Predictive assessment of deposition efficiency is in good agreement with experiments.